Révoltées : le corps dans l’œuvre de deux artistes colombiennes des années 70 - Adriana Pena Mejia (Les Cahiers ALHIM)
Taking into consideration the works of two women visual artists who we interviewed, this paper aims to explain the episodic and ambiguous interactions that these artists had with feminist ideas during the 1970s. This was a pivotal period for Colombia in three ways: the government opted for repression, guerrillas controlled the urban areas, and feminist groups spread to the country’s main cities. They did not have an important impact on the local art scene: in fact, most of the women visual artists considered these groups too radical. When they appeared, drawing was revitalized, artists tested news materials and the body took on new meanings. In a context of artistic renaissance and sexual liberation, the question of the female body progressively conquered the local artistic production. Whether examined by activists or by sceptics, this question and its generalization reveal the scope of the feminist ideas.